2012
DOI: 10.1258/ebm.2012.012014
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and etiology of community-acquired pneumonia in fever outpatients

Abstract: The purpose of this study was to analyze the incidence, etiology and clinical characteristics of community-acquired pneumonia (CAP) among outpatients with sore throat and/or cough, and thus to provide theoretical basis for timely and accurate diagnosis and treatment for CAP. We used chest X-rays for fever (a temperature greater than 37.5°C) patients, who were recruited since 2007, presenting with sore throat and/or cough. The patients' age, gender, days of fever, respiratory symptoms (e.g. cough and sputum), p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…Regarding preparation of ORS 30.98% mothers had good knowledge, 47.22% mothers had average knowledge and rest 21.79% had poor knowledge as depicted above. Similarly, as mentioned above 30.98% mothers were able to mention all the steps for the correct and complete preparation of ORS solution which is Similar to the other studies which found approximately 20% to 50% of the mothers were able to prepare ORS solution correctly and completely 20,21,22,23 . This may be because of moms' absence of related knowledge, an absence of legitimate training about the concerned issues and their ethnicity itself 23,24 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Regarding preparation of ORS 30.98% mothers had good knowledge, 47.22% mothers had average knowledge and rest 21.79% had poor knowledge as depicted above. Similarly, as mentioned above 30.98% mothers were able to mention all the steps for the correct and complete preparation of ORS solution which is Similar to the other studies which found approximately 20% to 50% of the mothers were able to prepare ORS solution correctly and completely 20,21,22,23 . This may be because of moms' absence of related knowledge, an absence of legitimate training about the concerned issues and their ethnicity itself 23,24 .…”
Section: Discussionsupporting
confidence: 82%
“…This means 328 loose bowels passing consistently per day and 13 consistently per hour. To be seen from [11][12][13][14][15][16][17][18][19][20][21][22][23] July, the Health Ministry propelled the across the nation 'Increased Diarrhoea Control Fortnight' (IDCF) 2 under which diff erent exercises have been arranged including visits by Accredited Social Health Activist (ASHA) specialists to every single such family unit which have kids younger than fi ve. "ASHA specialists will visit all family units with kids beneath fi ve years old for preparation and diff erent aspect of ORS the ORS.…”
Section: Introductionmentioning
confidence: 99%
“…Another multicenter study on pathogenic agents in 665 adult patients with CAP in China between December 2003 to November 2004 showed that M. pneumoniae was the most common type of pathogen (20.7%) [19]. Bao et al also found M. pneumoniae as the top etiological pathogens among 402 fever outpatients with CAP in China from January 2007 to January 2008 [20]. In our study, M. pneumoniae was the second most prevalent etiologic agent at 18%, indicating that attention should still be paid to M. pneumoniae infections in adult CAP outpatients in China.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the results of several epidemiological surveys of CAP conducted in Chinese adults have shown that Mycoplasma pneumoniae and Streptococcus pneumoniae are important pathogens of CAP in adults in China . Other common pathogens include Haemophilus influenzae , Chlamydia pneumoniae , Klebsiella pneumoniae and Staphylococcus aureus ; but Pseudomonas aeruginosa and Acinetobacter baumannii are infrequently isolated . In China, only a small number of cases of community‐acquired methicillin‐resistant S. aureus (CA‐MRSA) pneumonia are reported in children and teenagers .…”
Section: Section 1 Definition and Diagnosis Of Capmentioning
confidence: 99%